Performances of a VIPA-based spectrometer for Brillouin scattering experiments in the diamond anvil cell under laser heating. Issue 3 (3rd July 2022) - Forestier, A.; Weck, G.; Datchi, F.; Loubeyre, P.
ABSTRACT: VIPA-based Brillouin spectroscopy is implemented for in-situ measurements at high pressure and temperature in laser-heated diamond anvil cells. Its performances are compared to those of the widely used Tandem Fabry–Perot instrument. A significant reduction of the collection time is in particular enabled. The usefulness of VIPA-Brillouin spectroscopy for High Pressure studies is here illustrated by revisiting the nitrogen melting curve up to 45 GPa. VIPA-Brillouin spectroscopy has the potential to become an important platform to investigate the equation of state properties of warm dense molecular systems.